KEADILAN RESTORATIF TERKAIT PENYELESAIAN TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN KORBAN MENINGGAL DUNIA - Si Putu Hendra Pratama; Si Ngurah Ardhya (Jurnal Komunikasi Hukum, 2023)
The development of society and advances in the field of technology also encourages progress of the field of transportation, it is clear that progress is so rapid that it is necessary to have a rule that regulates traffic, where the regulation aims to create an orderly situation in traffic . Regulations regarding traffic are contained in the Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation. Traffic accident cases are processed by criminal justice procedures in accordance with applicable laws and regulations as stated in article 230 of the Traffic and Public Transportation Law, but the legal facts are ambiguity in the settlement of traffic accident cases where the settlement is resolved through a judicial process and some are resolved without going through a legal process based on peace. Then can Restorative Justice be applied to traffic accidents that result in the victim's death ? And how is the validity of the peace decision on handling accident crimes based on Police Restorative Justice if it is related to the provisions of article 230 in conjunction with 235 paragraphs (1) of Law Number 22 of 2009 concerning Road Traffic and Transportation ? And to answer these problems, it is necessary to conduct discussions relating to norms in law and examine various kinds of formal legal rules, so that they can provide input and limitations in legal science and criminal law in general and in particular in order to achieve justice and certainty in case settlement. traffic accidents that resulted in the victim's death.